Comparative study of the efficiency of residual cooking oil treatment with sodium hypochlorite and activated charcoal (Research, Society and Development, 2024)
Brazil stands out for its production of oilseeds such as soybeans, which is largely used in the development of cooking oil. The increasing use of these oils brings great concern for the environment, as their production becomes more difficult with each reheating during the frying process. Research shows that one liter of Residual Frying Oil (RFO), dumped into water bodies, contaminates around twenty thousand liters of water, one way to minimize this environmental impact is recycling the RFO to produce derivative products such as soap and biodiesel. The goal of this paper was treating the RFO with conventional clarification methods, such as treatment with sodium hypochlorite (NaClO), activated carbon (AC) and the two combined treatments to evaluate the parameters of humidity, acidity index, saponification index (SI) and unsaponifiable matter (UnsM) from the treated waste and also implement the best way to dispose of the effluent generated in the treatment with NaClO. This work finds that the treatments used, despite being clarification methods, are also efficient in improving the aforementioned parameters and can provide better overall quality to the RFO. Among the samples analyzed, it was found that the best treatment, in terms of quality improvement, was the combination of the treatments with NaClO and AC, which provided a reduction in all evaluated parameters, conferring quality to the RFO and, consequently, a possible gain in quality for the derived product that can be manufactured.